Pengaruh Beban Kerja, Pemahaman Teknologi Informasi Dan Kompetensi Terhadap Kinerja Pegawai Pengelola Dana Alokasi Khusus (Dak) Pemerintah Provinsi Kepulauan Riau Dengan Komitmen Organisasi Sebagai Variabel Intervening - Endang Irmarita, Yani; Wibisono, Chablullah; Gita Indrawan, Mohamad (Program Studi Manajemen FEBM UMRAH, 2024)
The realization of DAK in Riau Islands Province shows a fluctuating trend, namely the fluctuation ofthe DAK ceiling and budget. Based on the above phenomenon, the reporting of Special Allocation Funds is based onthe principle of accountability and commitment and quality of human resources in carrying out tasks andunderstanding of the OM SPAN application is also important in the management of DAK Province. The purpose ofthis study was to analyze the Workload on the performance of DAK managers intervening with organizationalcommitment in Riau Islands Province. Analyze Competence on the performance of DAK managers intervening withorganizational commitment in Riau Islands Province. Analyze Mastery of Information Technology on theperformance of DAK managers intervening with organizational commitment in Riau Islands Province. The testing ofthe research hypothesis was carried out using the Structural Equation Model (SEM) approach based on PartialLeast Square (PLS). PLS is a structural equation model (SEM) based on components or variants. The results of thestudy In the relationship between Workload (X1) and Performance (Y) there is a significant relationship in themodel. The results of this study can be concluded that high Workload intervening with organizational commitmenthas an effect on Performance. The results of this study can be concluded that Competence intervening byOrganizational Commitment has an effect on Work. It can be interpreted that the original sample has a positivevalue, meaning that there is a positive relationship in the model. The results of this study can be concluded thatMastery of Information Technology intervening by Organizational Commitment has an effect on Performance.